(untitled) (CAHIERS MAGELLANES-NS, 2024)
Background: Asthma is a chronic inflammatory disease of the airways, it results from a combination of genetic predisposition and environmental factors. Chronic Obstructive Pulmonary Disease (COPD) is a progressive lung disease characterized by persistent respiratory symptoms and airflow limitation. PLA2 catalyzes the hydrolysis of membrane phospholipids, releasing arachidonic acid, which is a precursor for the synthesis of pro-inflammatory eicosanoids, such as leukotrienes and prostaglandins. Methods: we performed Case-Control study compressing (n=120) including asthmatic patients (n=30) and COPD patients (n=30) with apparently healthy control subject group (n=60). Results: The mean ± SD age of patients with Asthma were (34.60± 8.47 years) and in the Chronic Obstructive Pulmonary Disease were (41.83± 8.36 years) there was no a significant difference between groups patients. The mean PLA2 levels with standard deviation (Mean± SD) are (44.29± 15.41) for Asthma, (55.50± 16.48) for COPD, and 22.13± 6.67 for Control. The statistical significance (Pr > F(Model)) is highly significant for Asthma (p < 0.000001), indicating a strong association between Asthma and PLA2 levels. However, for COPD and Control groups, the p-value is not provided, necessitating further analysis or interpretation to understand the significance of these results. The mean LTB4 levels with standard deviation (Mean± SD) are (116.39± 35.72) for Asthma, (148.47± 41.18) for COPD, and (55.16± 22.26) for Control. The statistical significance based on ANOVA (p < 0.000001) is highly significant for Asthma, suggesting a strong association between Asthma, COPD and Control groups. The mean PGI2 levels with standard deviation (Mean± SD) are (93.84± 16.66) for Asthma, (82.87± 13.58) for COPD, and (124.74± 20.10) for Control. The statistical significance based on ANOVA (p < 0.000001) is highly significant for Asthma, suggesting a strong association between Asthma, COPD and Control groups. Conclusion: Both serum levels of Phospholipase A2 and LTB4 a significant increased in patients with Asthma and Chronic Obstructive Pulmonary Disease compared with control and level decreased in patients with Asthma and Chronic Obstructive Pulmonary Disease compared with control, this finding supporting role of Phospholipase A2, LTB4 and PGI2 in patients with Asthma and Chronic Obstructive Pulmonary Disease, and suggesting that Phospholipase A2, LTB4 and PGI2 have an important role as Asthma and Chronic Obstructive Pulmonary Disease.